2018
DOI: 10.3122/jabfm.2018.05.170400
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Analgesia and Any Vaginal Laceration

Abstract: Patients who received epidural analgesia experienced fewer vaginal lacerations. There was no increase in OVD in patients who received epidural analgesia. Patients who delivered at a suburban hospital staffed by family medicine residents experienced fewer lacerations than those delivering at an urban hospital staffed by Obstetrics and Gynecology residents after controlling for race and other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
2
3
1
Order By: Relevance
“…Previous studies reported that no significant relationship between epidural usage and genital tract trauma [41][42][43]. Timothy et al even reported that epidural was negatively associated with laceration [44]. Compared with our study (the sample size is more than 4 million), the sample size of these previous studies was very small, the lowest is only about 200 [43] and the highest is less than 6000 [42].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Previous studies reported that no significant relationship between epidural usage and genital tract trauma [41][42][43]. Timothy et al even reported that epidural was negatively associated with laceration [44]. Compared with our study (the sample size is more than 4 million), the sample size of these previous studies was very small, the lowest is only about 200 [43] and the highest is less than 6000 [42].…”
Section: Discussioncontrasting
confidence: 84%
“…Compared with our study (the sample size is more than 4 million), the sample size of these previous studies was very small, the lowest is only about 200 [43] and the highest is less than 6000 [42]. In addition, Timothy et al's study included operative vaginal delivery as a mediator in the regression model [44], possibly resulting in overadjustment [45], and failing to correctly estimate the total effect of epidural analgesia. Changes in obstetric management could mediate the associations found in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…A higher birthweight was found in the EA group, although this result was not related to an increased rate of episiotomy performed or to a worse extent of vaginoperineal tears. Myrick et al 45 confirmed our findings in their recent research. Concerning the 2 shoulder dystocia cases recorded, both were without any neonatal consequence, neonatal birthweights exceeded 4000 g, and none of their mothers had diabetes mellitus.…”
Section: Discussionsupporting
confidence: 91%
“…Wassen et al showed that with increasing EA rates from 7.7% to 22% over ten years in the Netherlands, no similar increase in instrumental delivery was accompanied, 27 questioning the role of EA as a risk factor. Instrumental delivery is a known risk factor for higher grade perineal lacerations, 28,29 although the differences between groups in our study were quite close (2.8 vs. 3.2%) and are comparable to the literature [30][31][32] even with a more than twofold higher instrumental delivery rate with EA. The effect of EA on perineal lacerations is controversially reported, depending on the collective with beneficial, 28,31,33 negative 34 or no impact.…”
Section: Discussionsupporting
confidence: 82%